AST/ALT ratio, APRI, and FIB-4 compared to FibroScan for the assessment of liver fibrosis in patients with chronic hepatitis B in Bandar Abbas, Hormozgan, Iran - Seyed Hamid Moosavy; Ebrahim Eftekhar; Parivash Davoodian; Abdolazim Nejatizadeh; Mohammad Shadman; Shahram Zare; Mirza Ali Nazarnezhad (BMC Gastroenterology, 2023)
Abstract Background Chronic hepatitis B (CHB) is a significant risk factor for liver-related disorders. Hepatic fibrosis staging by liver biopsy in these patients can lead to complications. This study aimed to compare aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio, AST to platelet ratio index (APRI), and fibrosis-4 (FIB-4) with FibroScan results for the evaluation of hepatic fibrosis in CHB patients. Methods This cross-sectional study included patients with CHB referred to the outpatient clinics of Bandar Abbas, Hormozgan, Iran, in 2021. The age and sex of the participants were noted. FibroScan evaluation was done for all subjects. Moreover, AST, ALT, and platelet counts were measured in their blood samples within one month of the FibroScan evaluation. Results Of the 267 CHB patients evaluated in the present study (mean age: 45.45 ± 18.16 years), 173 (64.8%) were male. According to FibroScan results, 65 CHB patients (24.3%) had F1, 53 (19.9%) F2, 38 (14.2%) F3, and 20 (7.5%) F4 liver fibrosis. There was a significant correlation between FibroScan results and the three indices of AST/ALT ratio, APRI, and FIB-4 (P < 0.001), with the strongest correlation between FibroScan results and APRI (r = 0.682). With an area under the receiver operating characteristic (AUROC) curve of 0.852 (95% confidence interval [CI] 0.807; 0.897, P < 0.001), APRI ≥ 0.527 had the best diagnostic accuracy (77.15%) for the detection of any grade of liver fibrosis. Although the AUROC curve of APRI and FIB-4 was similar (0.864) for distinguishing between F3/F4 and F0-F2 of liver fibrosis, FIB-4 had the best diagnostic accuracy (82.02%). Conclusions APRI can rule out 95.4% of F3/F4 of liver fibrosis and rule in any grade of liver fibrosis in CHB patients by 90.78%. Therefore, APRI appears to be the best substitute for FibroScan in the assessment of liver fibrosis in patients with CHB.